Development and evaluation of a scheme system of joint prevention and control of PM2.5 pollution in the Yangtze River Delta region, China. (1st December 2020) - Wang, Yangjun; Liu, Ziyi; Huang, Ling; Lu, Guibin; Gong, Youguo; Yaluk, Elly; Li, Hongli; Yi, Xin; Yang, Liumei; Feng, Jialiang; Ivey, Cesunica; Li, Li
Abstract: Although many efforts have been done to reduce PM2.5 pollution in recent years, there are still many nonattainment cities in East China for national standards. How to collaborate with surrounding cities to reduce PM2.5 has been a critical issue for all nonattainment cities. In this work, a framework of developing a practical scheme system of joint prevention and control of PM2.5 pollution based on data mining technologies was presented. Moreover, one specific scheme system for Yangtze River Delta region was developed and evaluated by five indicators. The results indicate that the scheme system was divided into three grades depending on pollution levels except for summer with two grades. The heavier the PM2.5 pollution was, the higher the grade was recommended to be implemented along with low grades. Moreover, more city-clusters were involved in each grade in winter than any other season. For Grade one in winter, the city-cluster with Xuzhou and Suqian was the most urgent to control emission jointly; the city-cluster with Suzhou and Shanghai was linked to the biggest impact on health, but for integrated indicator, the city-cluster with Nanjing and Changzhou ranked first. These results not only enable an enriched understanding of the significance of PM2.5 control in city-clusters, but also accelerate PM2.5 reduction for all nonattainment cities by collaboration with their most correlated cities in this region. Highlights: A scheme system of joint prevention and control of PM2.5 pollution was developed. This specific scheme system depended on seasons and PM2.5 pollution levels. The scheme system was designed to reduce PM2.5 pollution for nonattainment cities.